Superior Vena Cava Syndrome and Colon Carcinoma: A Report of a Multifactorial Association. (25th February 2015) - Espírito Santo, Joana; Coutinho, Inês; Pimentel, Ana; Garcia, Rui; Marques dos Santos, Rui
Abstract : Introduction . Superior vena cava (SVC) syndrome results from the obstruction of blood flow through the SVC, having distinct pathophysiological underlying mechanisms. Cancer is associated with an increased risk of thromboembolism that varies according to patient-, tumor-, and treatment-related factors. An individualized clinical approach is important to pursue the accurate diagnosis of the underlying pathology causing thromboembolism in cancer patients. Case Presentation . The authors present a case of a 58-year-old male with an infrequent presentation of an unknown colon carcinoma, who has never had any symptom until he was hospitalized with the diagnosis of superior vena cava syndrome and pulmonary thromboembolism. The patient had an advanced disease by the time of diagnosis and molecular alterations contributing to abnormal hemostasis. He presented venous and arterial thromboembolism and developed disseminated intravascular coagulopathy after surgery, anticoagulant and transfusion therapy, dying 40 days after the hospitalization. Conclusion . The authors discuss thromboembolic disease and tumor metastasis roles in a cancer patient with SVC syndrome. Thromboembolism in a malignancy context is a challenging clinical entity. A multifactorial perspective of the thrombotic disease is warranted to approach thromboembolism risk and stratify patients suitable to receive adequate anticoagulant prophylaxis and targeted therapies, aiming to improve clinical prognosis.